An analysis on the mobile readiness of American Fortune top 500 companies' websites - Juyun Cho; Jongheon Kim (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
As more and more users are getting to use smart phones and tablets due to the ease of use, portability, and a large range of free applications, organizations that use their websites as a vehicle to deliver important information to users should revisit their sites to check for any potential improvement for increasing mobile device users. This paper analyzes mobile readiness of the American Fortune top 500 company's websites. The performance of sites for various mobile devices is measured by several ways that scrutinize an actual page loading speed and 38 technical elements of the sites. Improving a performance of a website can significantly impact a user experience as well as organization's potential profit.
Keywords: 650; Mobile Readiness; Usability; Responsive Web Design; Page Weight; Fortune 500 Companies; Websites for Mobile Devices; Mobile Ready Score